Mini Review on the Use of Clinical Cancer Registers for Prostate Cancer: The National Prostate Cancer Register (NPCR) of Sweden - Cazzaniga, Walter (Front Med (Lausanne), 2019)
Given the increasing prevalence of cancer, it is vital to systematically collect data in order to monitor disease trends and quality of cancer care. For this purpose, clinical cancer registries have been developed in some countries. These registers are intended to be used as a basis for quality assurance and quality improvement, but they also constitute a rich resource of real world data for research. The aim of this mini-review was to describe the structure and the organization of the National Prostate Cancer Register (NPCR) with some examples on how data in NPCR have affected prostate cancer care in Sweden.